2015
DOI: 10.1128/jcm.03527-14
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Phylogenomics of Shigella Species: a Pathway to Diagnostics

Abstract: g Shigellae cause significant diarrheal disease and mortality in humans, as there are approximately 163 million episodes of shigellosis and 1.1 million deaths annually. While significant strides have been made in the understanding of the pathogenesis, few studies on the genomic content of the Shigella species have been completed. The goal of this study was to characterize the genomic diversity of Shigella species through sequencing of 55 isolates representing members of each of the four Shigella species: S. fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 58 publications
9
109
0
Order By: Relevance
“…The comparison analysis in this study showed that Ͼ98% of the kmer ID results were concordant with the results derived by traditional methods. The isolates of S. flexneri belonging to ST1753, misidentified by TB&S as S. boydii due to a dysfunctional wzx [1][2][3][4][5] gene, highlight one of the problems with using serology to identify Shigella to the species level (15). Historically, S. boydii and S. dysenteriae were differentiated biochemically by the mannitol test, and the relationship between these two species within CC145 and CC288 demonstrates that separating species based on one test can be misleading with respect to their true phylogenetic relationship.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison analysis in this study showed that Ͼ98% of the kmer ID results were concordant with the results derived by traditional methods. The isolates of S. flexneri belonging to ST1753, misidentified by TB&S as S. boydii due to a dysfunctional wzx [1][2][3][4][5] gene, highlight one of the problems with using serology to identify Shigella to the species level (15). Historically, S. boydii and S. dysenteriae were differentiated biochemically by the mannitol test, and the relationship between these two species within CC145 and CC288 demonstrates that separating species based on one test can be misleading with respect to their true phylogenetic relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) were detected relative to the completed genome sequence of the phylogroup F laboratory isolate E. coli IAI39 using the In Silico Genotyper (ISG) (34), which uses MUMMER v.3.22 (35) for SNP detection. The SNP sites that were identified in all genomes analyzed were concatenated and used for phylogenetic analysis as previously described (33). A maximumlikelihood phylogeny with 100 bootstrap replicates was generated using RAxML v.7.2.8 (36) and visualized using FigTree v.1.4.2 (http://tree.bio .ed.ac.uk/software/figtree/).…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenomic analysis of 210 AEEC genomes and a diverse collection of 25 E. coli and Shigella genomes was performed as previously described (33,34) (see Table S1 in the supplemental material). These isolates are identified as attaching and effacing E. coli (AEEC) based on the molecular presence of the locus of enterocyte effacement (LEE) region and have not been functionally examined for the attaching and effacing phenotype.…”
Section: Methodsmentioning
confidence: 99%
“…The genome sequences of these species have undergone substantial reduction, with multiple metabolic pathways becoming lost. One such victim of genome reduction is the methylcitrate pathway, which appears to have been specifically deleted from many of these enteroinvasive pathogens, although it is found in all other E. coli genomes [43,44]. Additionally, four genes (prpDBCE) found in Campylobacter coli but not in C. jejuni are involved in the methylcitrate cycle, which could account for the enhanced ability of C. coli strains to grow on odd-chain fatty acids compared with C. jejuni [45,46].…”
Section: Enterobacteriamentioning
confidence: 99%